Tomme høje - Andersen, Harald (Kuml, 1951)
Empty Tumuli Empty tumuli - by which is meant tumuli in which no human remains have ever been interred - are an often-occurring phenomenon of the Scandinavian Iron Age, a remarkable feature being that it is often the very large barrows which are empty. The largest tumulus in Norway (and in Scandinavia), Raknahaugen, and the largest tumulus in Denmark, the Jellinghøj, are included under this grouping. Other well-known empty tumuli are Slotsbjergbyhøj and Himlingøjehøj, Farmannshaugen and Sølyshaugen, all of which, together with a number of similar mounds, it has been possible to date to the Iron Age. To this category must also be added a large number of undated tumuli, while empty barrows raised over earlier burial mounds, or empty barrows in the upper part of which secondary burials have later taken place, are likewise included. An investigation of the structure of the Iron Age tumuli with particular attention to explaining the riddle of the empty barrows shows three characteristics as occurring repeatedly; a flat top, a post erected within and in the centre of the tumulus, and a large stone placed on its top. These characteristics appear to occur most commonly in the period from about 300 AD to about 1000 AD, though it is possible that they have their roots in Bronze Age traditions. Of them the flat top is of most common occurrence in Iron Age tumuli (figs. 3, 5, 6 & 8) though it is not found in every case. Well-known examples of this type are the large Swedish “royal barrows” from the Period of Migration· (figs. 8 & 9). A remarkable feature is that in Denmark flat-topped tumuli occur very frequently in chuchyards, the probable explanation being a desire to render the heathen institution harmless by incorporating it in the Christian consecrated area (figs. 10, 11 & 12). The central post is known from the Jelling tumulus and from that at Slotsbjergby, from Farmannshaugen and from a number of other tumuli, both empty and containing interments (figs. 3, 13, 14, 15, 16, 17 & 18). The Arabian geographer lbn Fadlán travelled in 921 AD to the region around the Volga and there had the opportunity to view the cremation of a Scandinavian chieftain. He describes how, after the cremation, the chieftain's followers built a tumulus "and raised in its centre a large wooden post on which they wrote the name of the dead man and of the king of the Russians". Centre posts are also recorded from west German tumuli; these posts are, however, generally from an earlier period than the Scandinavian, occur mainly in smaller barrows and appear to have projected above the summit of the mound (fig. 19). The stone on the top is known from Iron Age tumuli over the whole of Scandinavia (figs. 4, 8, 9, 15, 16, 20 & 21). The significance of these constructional features can be summarised as follows: the top of the tumulus was probably flattened to allow the tumulus to be used for certain ceremonies, partly of a political nature (proclamation of laws, judicial proceedings, etc.), as the sagas frequently describe, and partly of a religious nature (memorial services and offerings to the dead) as objects found and folk-traditions appear to suggest. The stone on the top of the tumulus was probably to bind the soul of the person buried there to the barrow. It formed the central point of the ceremonies which took place there and in its later form was presumably first and foremost a memorial stone for the dead. There exists the possibility that the latest of these stones, the actual “bautasten”, were in fact rune stones, the runes, however, being painted instead of carved. The central post appears, at least originally, to have had the same functions as the “bautasten”; though in the case of Scandinavian tumuli it has undoubtedly also served the practical purpose of providing a datum point for measurements for the construction of the tumulus. When we come to consider the empty tumuli one question in particular demands an answer: why are the tumuli empty? Now in the cases where an interment has taken place centrally in the upper part of the otherwise empty mound there is reason to believe that this is the principal burial of the tumulus, the explanation probably being that the person buried there built his own barrow during his lifetime. In the case of the tumuli which are completely empty the explanation most frequently put forward is that they are cenotaphs raised in memory of persons who had died far away. An alternative possibility is suggested by the descriptions in legends of dead heroes being placed on board a ship which was then launched out upon the waters, pilotless and in some cases in flames. Mention is also made of the custom of strewing the ashes of the dead upon the water. Memorial mounds may well have been raised in connection with such disposal of the dead, thus giving rise to empty tumuli. Moreover the possibility cannot be discounted of such archaeologically untraceable customs being in general use, thereby providing an explanation of the paucity of graves which can be noted over a large part of Scandinavia during long stretches of the Iron Age. Finally a further possibility presents itself which would provide an explanation of the emptiness of the Jellinghøj and of other large tumuli. This is that the body was placed in a surface mortuary house built on the flat top of the tumulus. Excavations on the top of the Jellinghøj revealed the remains of a building (fig. 22), under the uprights of which flat boards were laid, suggesting that the building was erected while the tumulus was newly built and still soft, in other words contemporaneously with the tumulus. This building may have held the body of King Gorm who according to tradition and to the rune stone standing near the tumulus was buried here. This theory can be supported in various ways. A number of cases of "surface graves" can be adduced; for example, in the case of a little Swedish tumulus at Ulltuna ship's nails, grave furnishings and unburnt animal bones were found spread over the whole mound immediately under the ground surface (fig. 23). Only over the actual summit of the mound lay two rows of nails in order. Undoubtedly the ship was set up in plain view on the top of the tumulus with its contents consisting of the body, animal sacrifices and grave goods, corresponding exactly, apart from the placing of the ship, to the Swedish Vendel graves. Similarly the ship belonging to the well-known boat-chamber grave at Hedeby (fig. 24) certainly lay uncovered on the ground surface; it was, however, hardly a grave in its own right but should rather be regarded as a colossal gravegift. Surface "grave-houses" erected over an interment place are known in one confirmed and several less certain Danish examples. (The confirmed case, from the village of Farre, will be found described elsewhere in this publication.) These mortuary houses have also been found in Germany (Nienborg, Eppingawehr), while similar constructions, in this case small wooden houses placed on top of the grave (fig. 26) are known from Christian churchyards in Sweden and the Baltic lands. The type of mortuary house which is relevant to the question of the empty tumuli, that where the body is laid inside the building, is not confirmed by uncontroversial discovery, which in view of the likelihood of destruction by robbery or by the action of the weather is understandable; it is, however, described from two literary sources, one Icelandic and the other Norwegian. A further type of "house-grave" should be recorded, though perhaps idealogically unconnected with the true mortuary houses above described. This is the grave placed under the dwelling-house. A very few discoveries in Norway and Denmark illustrate this type of burial, which is also mentioned in several source-books. The material adduced strengthens the probability that a burial practice such as that suggested has existed. The Ulltuna discovery of a grave-ship with full grave furniture (including certainly the body) placed on top of a tumulus appears to correspond exactly to the tumulus with a mortuary house on top; for it is reasonable to suppose that grave-ship and grave-house could occur as parallel customs on top of the tumuli in the same way as grave-ship and grave-chamber occurred as parallel customs within the tumuli. This suggested burial custom also gives a reasonable explanation of why the empty tumuli are often very large - it must be because kings and chieftains built their own tumuli. In the case of the Jellinghøj this explanation harmonizes the claims of tradition, the witness of the rune stones and the evidence of excavation. Harald Andersen